TEACHERS’ AND STUDENTS’ PERCEPTIONS OF THE USE OF SMARTPHONE IN THE ENGLISH CLASSROOM AT SMPN 18 MAKASSAR - Nurmiati, Nurmiati; Farahdiba, Syarifah; G, Hasriani (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This study aims to find out whether teachers and students have a positive or negative perception of the use of smartphones in the English classroom. This research applies the qualitative method. The participants in this research were 2 teachers and 10 students from class VII of SMPN 18 Makassar in the academic year 2022/2023. The participants were chosen by using a purposive sampling technique. The instrument used in this research was an interview and documentation. The results of this research indicate that the use of smartphones in learning English in the classroom receives a lot of positive than negative perceptions from teachers and students. The common positive perceptions mentioned by the teachers are increasing students' motivation, seeking additional information or material, and attracting students’ attention. The negative perception that is commonly mentioned by teachers is the quota runs out, and students are addicted to games. Meanwhile, the common positive perceptions mentioned by the students are easy to find material or information, increased students’ motivation, more fun in learning, and easy to share or communicate with teachers. The negative perception that is commonly mentioned by students is the quota running out, internet error, blurry eyes, and cheating habit.